Comparative Arguments and Ethical Analysis: Selective Abortion and Eugenics - Tomás Hernández Mora (Revista Filosofía UIS)
This article aims to ethically evaluate selective abortion and eugenics, as well as to analyze the practical feasibility of comparing both terms to legitimate, or not, the prohibition of this form of interruption of pregnancy. To this end, the concept of “abortion” will be studied, emphasizing the notion of “selective abortion”. Likewise, the concept of “eugenics”, its origin, objectives, and consequences will be explained. Next, several arguments comparing selective abortion with eugenics will be presented, along with possible counterarguments. Finally, the inviolability of human life, the humanity of the fetus, the ethical viability of the so-called “liberal eugenics”, and some conclusions about the practical plausibility of making this comparison will be exposed.